God's Saving Purpose and Prayer for All the Departed - Gould, James B. (2012)
Throughout much of church history Christians have prayed for the dead. Historical, liturgical and pastoral contexts suggest that, while Anglicans may pray for the continual growth of the faithful departed, we have seldom prayed for advancement from purgatory or deliverance from hell. In this paper I defend all three, noting where my argument departs from and intersects with historic Anglican positions. I offer an outline of theology from the perspective of death, arguing that prayer for all the departed is one aspect of a tightly knit web of doctrines including theology proper, creation, salvation and consummation. Petitions for all the dead are not inconsequential. Instead, the final destiny of human persons raise the most basic of theological questions, matters which go to the center of God's purpose in creating spiritual beings and redeeming sinful humankind.
Keywords: Universalism; Purgatory; prayer for dead; Hell; Heaven; Anglican